Theater and the investigation of the human being. The modern actor on stage...in the wake of Diderot (Itinera, 2021)
Can we say that the 18th century philosophe Denis Diderot and his theses of theatrical aesthetics are still relevant and viable on the modern theatre stage? The article elaborates on our contemporaneity to try to give an answer to this question, creating questionnaires-interviews with four professional actors with questions related to the key themes of Diderot's theatrical and artistic aesthetics, encountering the incredible actuality of the Diderotian vision. The idea of the actor's profession is, in its true essence, an aesthetic idea, thus stimulating a philosophical reflection based on all the great concepts of this discipline, highlighted by the theoretical and practical thought of Diderot and now investigated by the theatrical practice of contemporary actors: body, gestures, genius, interpretation, communication, expression.The sentiment of the Diderotian comédien on stage overcomes the distinction between a "warm", involved and passionate acting and a "cold", rational and controlled one, and declines its sensibility in a supra-individual meaning, in a concrete presentation of a model with a universal value but possible for the body of the actor on stage, therefore shared by spectators who observe the events happening on stage. In the same way, the modern actor trains on stage, organically and honestly, towards "becoming" in every moment and towards being legible, credible, creative, bringing to the stage actions full of questions that explore the possibilities of being human. In other words, becoming - as one of the actors interviewed in the questionnaire states in a very Diderotian way - «body of all bodies. A body that knows and can tell something universal and that makes vibrate inside the viewer the internal velvet that moves the soul. Even looking at something unrecognizable directly or consciously, I will feel narrated as a human being».
Keywords: Denis Diderot, theatre, acting, aesthetics of theatre, body.